Cultural Nature of Onomastic Language Units - Makhsudova, Holiskhon; Umida Ziyamukhamedova; Yoga Prihatin (Universitas Pancasakti Tegal, 2024)
In this article, onomastic linguistic units are analyzed from a linguocultural point of view. The influence of social factors on the language can be seen in the historical change and development of the processes of cultural and everyday life of a particular people, ethnicity, lifestyle, cultural relations, etc. In this context, the integration of the science of linguistics based on anthropocentric principles has led to an incomparable expansion of the object research. In particular, the problem of the relationship between language and culture has become one of the leading directions. In particular, there is a natural need for such an interpretation within the framework of onomastics.